PENGARUH PEMBERIAN RAGI ROTI ( Sacharomyces cerevisiae) DENGAN DOSIS YANG BERBEDA TERHADAP MINYAK KELAPA MURNI DENGAN METODE FERMENTASI - Demetriana Noni; Nur Aini Bunyani; Abdonia W. Finmeta; Maya F. Roman (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Coconut (Cocos nucifera L) is one of the plants that has high economic value because almost all of its parts can be used in human life. This research was conducted at the MIPA Laboratory on April 10 to May 10, 2025. The purpose of the research process was to determine the effect of giving Saccharomyces cerevisiae with different doses. The research method used in this study was a Completely Randomized Design (CRD) using 4 treatments and 3 replications containing 12 experimental units. Regarding treatment A0: 0 (without bread yeast) / 1 Liter of coconut milk, A1: 7 grams / 1 Liter of coconut milk, A2: 10.5 grams / 1 Liter of coconut milk and A3: 14 grams / 1 Liter of coconut milk. The data obtained were analyzed with a Variety Scale if they were significantly different then continued with the BNT test. The results of this study show that the highest yield with the addition of 7 grams of yeast/liter of coconut milk produces 100 ml of pure coconut oil, followed by without the addition of bread yeast. The lowest yield does not produce oil at the addition of 14 g/liter of coconut milk. The best dose of 7 g/liter of coconut milk is at this dose, fermentation takes place efficiently, so that pure coconut oil is formed well.